Kinetics of In-Situ Catalytic Pyrolysis of Rice Husk Pellets Using a Multi-Component Kinetics Model - Wusana Agung Wibowo; Rochim Bakti Cahyono; Rochmadi Rochmadi; Arief Budiman (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Ash-based catalysts, as low-cost materials, are applicable in biomass pyrolysis and play a role in lowering the activation energy. This study enriched the insights of different method of catalyst addition into biomass in the catalytic pyrolysis. The addition of rice husk ash as a catalyst into rice husk pellets allows for better solid-solid contact between the biomass and the catalyst, since the common methods were only solid mixing. This research aimed to investigate the thermal characteristics and kinetics of the biomass components (hemicellulose, cellulose, lignin) in the in-situ catalytic pyrolysis of rice husk pellets with the addition of husk ash. The three-independent parallel reaction kinetics model was used to calculate the kinetics parameters based on thermogravimetric analysis conducted at 303-873 K with various heating rates (5, 10, 20 K/min) and ash addition ratios (10:0, 10:1, 10:2). The thermogram shows that the pyrolysis of rice husk pellets was divided into two stages. Stage 1, ranging from 510-650 K, represented the decomposition of hemicellulose and cellulose, occurring faster with high mass loss, while Stage 2, starting at around 650 K, represented lignin decomposition, occurring more slowly with low mass loss. The catalytic activity of the ash was only apparent at high temperatures, where cellulose and lignin decomposition were more dominant. Activation energy, as a representation of catalytic activity for each component, was not always lower in catalytic pyrolysis. However, the average activation energy decreased with increasing heating rates and ash addition ratios. The addition of the catalyst slowed the decomposition of hemicellulose but accelerated the decomposition of cellulose and lignin. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).